Colonization resistance of vaginal secretion - Gruzevskiy, A. A. (Journal of Education, Health and Sport, 2019)
Vaginal contents - vaginal secretion - this is a serous vascular transudate, a secret of the glands of the mucous membrane of the canine of the cervix and large glands of the vagina front, of the leukocytes and of the epithelium of the corpus luteum [1]. The main chemical composition of the vaginal secretion is water, inorganic salts, proteins (albumins, immunoglobulins), carbohydrates, fatty acids, urea, lysozyme [2, 3, 8]. Physiological maturation of epithelial cells, accumulation of glycogen in them and securing the acidity of the vaginal secretion are affected by estrogen. To the protective mechanisms of the vagina are physiological white, the normal amount of which per day is up to 2 mg; A normal microflora of the vagina is present in the form of lactobacter bifidobacteria, which compete with the vaginal microflora for glycogen and create an acid medium. A key factor is the so-called "colonization resistance of the vaginal secretion," which includes the protective agents that enter humoral pathway here and are produced by local lymphoid tissue (IgA, IgM, IgG, lysozyme, a-lysines, complement, secretory IgA, etc.), bactericidal compounds hydrogen peroxide, lactic acid), cells of the immune system (leukocytes, macrophages, T- and B-lymphocytes) [4, 5, 6]. The purpose of the work was to study cellular and humoral indices at normal norms and at different levels of dysbiosis. The results of the correlation analysis showed that the content of IL10 in the vaginal secretion had strong direct relations with humoral and cellular factors of colonial resistance - IgA, sIgA, IgG2, lysozyme, phagocytic activity of leukocytes and the index of phagocytic activity of leukocytes, C3 and C4, γ-INF ( from r = 0.52 to r = 0.80; p <0.05 in all cases), and inverse - with all proinflammatory cytokines (from r = -0.68 to r = -0.77; p <0, 05 in all cases). Moreover, the positive association with the level of IL10 was with the level of lactobacillus (r = 0,56; p = 5,51E-26) and the main protein of myelin (r = 0,41; p = 3,15E-13), while with the indicator normobiota, the content of elective anaerobes and obligate anaerobes was negative (r = -0.49, r = -0.53 and r = -0.47, respectively, p <0.001 in all cases). This confirms the role of IL10 as a universal integrative regulator in the development of bacterial vaginosis.